4x-4=-5(7x-6)+83

Simple and best practice solution for 4x-4=-5(7x-6)+83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-4=-5(7x-6)+83 equation:



4x-4=-5(7x-6)+83
We move all terms to the left:
4x-4-(-5(7x-6)+83)=0
We calculate terms in parentheses: -(-5(7x-6)+83), so:
-5(7x-6)+83
We multiply parentheses
-35x+30+83
We add all the numbers together, and all the variables
-35x+113
Back to the equation:
-(-35x+113)
We get rid of parentheses
4x+35x-113-4=0
We add all the numbers together, and all the variables
39x-117=0
We move all terms containing x to the left, all other terms to the right
39x=117
x=117/39
x=3

You can always share this solution

See similar equations:

| (32/x)+6x=90 | | 32/x+6x=90 | | (-17-3r/2)=-19 | | (3-x)(4-x)-2=0 | | 1x^2-7x+2=-8 | | x4-15x2=16 | | f/4+75=158 | | 5x+13+4x+12=11x+3 | | (3x+5)/4-(2x-1)/3=2 | | 5x+13+4x+12+11x+3=180 | | 13f-72=760 | | 7f+49=434 | | 6m+21/2=33/2 | | (x+10)/2+3=2 | | x+10/2+3=2 | | 6x^2-9x-56.5=0 | | 33/2x-5-3=1/4 | | 5x+8-7x=15-17x+15x-7 | | 4(3x+4)=-4x+5 | | 6(4x-3)=9x+2 | | 5y-7+y+25=8y+20-4y | | 7c+13c=160 | | 5?(x-3)+8x=6x-5+x | | 3(1y-4)=28 | | 8.8x=44.0 | | 4x+6=-7x+1 | | 13x-9=-14 | | -7/3a=21 | | (x)+(x+1)+(x+2)=42 | | 3t2=16t-5 | | 12a^2-8a=0 | | 3a+2/5=1 |

Equations solver categories